Trade crisis? What trade crisis? - Kristian Behrens; Gregory Corcos; Giordano Mion (National Bank of Belgium, 2010)
We provide an analysis of the 2008-2009 trade collapse using microdata from a small open economy, Belgium. First, we find that changes in firm-country-product exports and imports occurred mostly at the intensive margin: the number of firms, the average number of destination and origin markets per firm, and the average number of products per market changed only very little. Second, econometric analysis reveals some composition effects in the intensive margin fall along firm, product and country characteristics. The most important factor explaining changes in exports is the destination country's growth rate of GDP. Had growth rates in 2008-2009 been the same as in 2007-2008, Belgian exports would have fallen by about 57% less than what we observe. Trade in consumer durables and capital goods fell more severely than trade in other product categories, which explains another 22% of the observed fall. Financial variables and involvement in global value chains have some explanatory power on the exports and imports fall respectively, but appear to have affected domestic operations in equal proportion. More generally, exports-to-turnover and imports-to-intermediates ratios at the firm level did neither systematically decrease nor reveal strong firm- or sector-specific patterns. Overall, our results point to a demand-side explanation: the fall in trade was mostly driven by the fall in economic activity. It is not a trade crisis - just a trade collapse.
Keywords: F01; F10; F14; 330; trade crisis; trade collapse; margins of trade; firm-level analysis; Belgium; Internationale Wirtschaftsbeziehungen; Internationale Wirtschaft; Wirtschaftskrise; Industrie; Kleine offene Volkswirtschaft; Belgien